PERANCANGAN APLIKASI PENGELOLAAN DATA KELUAR MASUK BARANG MENGGUNAKAN PHP DAN MYSQL - Azhar, Muhammad Farhan Dhika (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
Inventory data management in workshops is a vital component of business operations. Nevertheless, many workshops still rely on manual systems, which can result in errors, data loss, and inefficiencies. This study aims to design and develop a web-based inventory management application for workshops using PHP and MySQL. The application streamlines inventory data recording and management, enhancing efficiency and accuracy.The waterfall method is employed for system development, encompassing requirements analysis, design, implementation, and testing. The results demonstrate that the application functions effectively and meets user requirements. This application enables workshop owners to manage inventory data more efficiently, monitor stock in real-time, reduce errors, and improve customer satisfaction.